Pengembangan Game Pembelajaran Teori Atom Dasar Model RPG sebagai Pendekatan Pengenalan Pembelajaran Kimia Sekolah Menengah Pertama - Rizky Arief Shobirin; Riska Nurtantyo Sarbini; Putri Nur Rahayu (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
The purpose of developing chemistry learning game for basic atomic theory material was to help students' understanding as young learners to make it easier to understand and interesting to learn, bearing in mind the decline in interest in learning for young learners during and after the Covid-19 pandemic. This Game-based Learning was built using the RPG (Role-Playing Games) development model based on Quest-Driven Learning (QDL) for chemistry learning, that was basic atomic theory with the System Development Life Cycle (SDLC) as system development method. The RPG game genre was the basis for making software in the form of learning games, which referred to the Model Quest-Driven Learning approach which applies the concept of reward to the learning process. Provision of main learning materials in the form of main quests (basic atomic theories) and side-quests (development of chemistry that was still related to the atomic theories), in which new side-quests would available to be taken by students after completing each main quest of basic atomic theory learning. The results of the implementation of the game "Atom Man" were obtained assessment of the interest level of young learners of 90%, and interested in learning atomic and fun chemistry 90%. Students as young learners regarded the learning game "Atom Man" as just a game, school (school), and adventure (adventure) that helped students in learning basic atomic theory chemistry.